2017
DOI: 10.1002/2017jb014253
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of multiphase fluid imbibition in shale through synchrotron‐based dynamic micro‐CT imaging

Abstract: While substantial advances were made in pore system characterization in shale in the past decade, understanding of fundamentals of multiphase fluid flow in shale remains limited. The complexity of multiphase fluid flow in shale is related to many factors including nanoscale to submicron‐scale pore systems, differences in mineralogy and associated surface wettability, heterogeneity of these properties at different scales, and possible existence of microfractures. Previous work related to fluid flow, such as per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…Only less than 15 % of the fracture is filled by water, which shows its dominant oil‐wetting tendency. Peng and Xiao imbibition experiments via the dynamic imaging of multi‐phase fluid imbibition through the Eagle Ford shale support our results, as it indicates that the microfractures in Eagle Ford shale are generally oil‐wet. In the next step, we marginally increase the water pressure to simulate the early stages of the forced imbibition.…”
Section: Workflow Of Numerical Simulationsupporting
confidence: 77%
See 1 more Smart Citation
“…Only less than 15 % of the fracture is filled by water, which shows its dominant oil‐wetting tendency. Peng and Xiao imbibition experiments via the dynamic imaging of multi‐phase fluid imbibition through the Eagle Ford shale support our results, as it indicates that the microfractures in Eagle Ford shale are generally oil‐wet. In the next step, we marginally increase the water pressure to simulate the early stages of the forced imbibition.…”
Section: Workflow Of Numerical Simulationsupporting
confidence: 77%
“…Oil fills back the oil‐wet sections and the residual water mostly remains in the larger pores surrounded by oil, see Figure . The observations made by Peng and Xiao during immiscible oil and water displacements illustrate similar oil‐water residual patterns. By post‐processing the phase profiles and calculating the effective permeabilities, the tortuosity parameter (α) throughout the microfracture for both phases approaches zero.…”
Section: Workflow Of Numerical Simulationsupporting
confidence: 58%
“…Therefore, the proportion of macropores of coal is highly correlated to the TPI, and TPI could indicate the seepage characteristics of coal. The paleo-environment governs the degree of pore development by affecting the petrographic composition and content of macerals [12,[52][53][54][55][56][57][58]. Zhang et al studies have found that the macro-and mesopores are closely correlated to TPI with the R-cluster analysis method, while there are no data to support the specific relationship between pore and coal facies [20].…”
Section: Characteristics Of Coal Faciesmentioning
confidence: 99%
“…The tracer and micro-CT experiment was carried out using the synchrotron-based micro-CT imaging facility at beamline 2-BM of the Advanced Photon Source at Argonne National Laboratory. The basic steps are similar to those in Peng and Xiao (2017). One change is on the exposure time of each projection, which is extended to 160 ms from 100 ms in our previous work.…”
Section: Oil-phase Tracer Imbibition and Micro-ct Imagingmentioning
confidence: 99%
“…This method is applied to five samples from Wolfcamp and Eagle Ford Formations. This study builds on our previous work, in which the focus is mostly on water/oil displacement in microfractures and matrix in shale using only micro-CT and tracer imbibition (Peng & Xiao, 2017).…”
Section: Introductionmentioning
confidence: 99%